An Analysis of Students Speaking Constraints at Seven Grade in Islamic Junior High School of Darul Ulum - Abdul Jalal; Abd. Aziz Wahab; Zainuddin Zainuddin; Beny Hamdani (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractThis research is about the contraints of speaking skills in English. The purpose of this research is mainly to 1. describe the students' problems in speaking and 2. to describe effective solutions to overcome constraints in speaking, the participants of this study were 13 students who were at seven grade in Islamic Junior High School of Darul Ulum, the instruments used in this research were observation, interview, and documentation. After getting the data results, the researcher continued to analyze and determine the categories of speaking difficulties, and teacher constraints when teaching. The results of this research showed that 80% had difficulty with 20% learning as usual, the most prominent problems in the speaking process consisted of minimal vocabulary, poor pronunciation, and grammatical errors. Other factors include an unsupportive environment that causes students to not have enough motivation to learn English, teachers play an active role in overcoming problems such as providing vocabulary continuously, creating a pleasant learning atmosphere, and motivating students in speaking learning.Keywords: Student Contraints, Speaking, Islamic Junior High School of Darul Ulum